TIMP4 serves as a novel potential prognostic biomarker for oral squamous cell carcinoma - Lian Zhou; Changlin Tang; Renjie Shuai; Binxin Chen; Xinyan Yang; Yungang He; Jian Wu (Scientific Reports)
Abstract The abnormal expression of tissue inhibitor of metalloproteinase 4 (TIMP4) is associated with multiple human cancers. However, the role of TIMP4 in oral squamous cell carcinoma (OSCC) remains elusive. Therefore, this study explored the expression profile and prognosis of TIMP4 in OSCC. Tumor and adjacent non-tumor tissues were collected from OSCC patients, and protein expression of TIMP4 was detected through immunohistochemistry (IHC) and positive cell counting. Additionally, The Cancer Genome Atlas-Head and Neck Squamous Cell Carcinoma (TCGA-HNSCC) dataset was used to analyze TIMP4 expression further to determine its relationship with HNSCC clinical characteristics. Kaplan-Meier analysis was used to evaluate survival and prognosis. Meanwhile, the Tumor Immune Estimation Resource (TIMER) database was employed to assess the correlation between TIMP4 expression and tumor immune infiltration. Computational tools were also applied to investigate the involvement of TIMP4 in cancer pathways. Results showed that TIMP4 was decreased in OSCC and HNSCC compared with normal tissues. The decrease in TIMP4 was associated with cancer metastasis, immune suppression and HPV positive, clinical staging. Overall, these findings demonstrate that TIMP4 is significantly reduced in OSCC and HNSCC, and associated with a poor prognosis. Additional investigations are warranted to fully understand the therapeutic potential of TIMP4 in OSCC.